Panniculitis in Anti-MDA-5 Positive Juvenile Dermatomyositis: A Case Report - Semra Ayduran; Gulsah Kilbas; Saadet Nilay Tigrak; Selcuk Yuksel; Erdem Comut; Serkan Turkucar (Journal of Nepal Medical Association)
Panniculitis is a rare clinical finding in dermatomyositis. There are few reported cases in the medical literature. In this report, we describe a 17-year-old male patient with anti-MDA5 positive hypomyopathic dermatomyositis who, eight months after diagnosis, presented with indurated nodules on the right forearm and right thigh despite methotrexate and monthly intravenous immunoglobulin treatment. A skin biopsy revealed lobular panniculitis with lymphocytic infiltrate. His lesions were successfully controlled with hydroxychloroquine and azathioprine. This article presents a case regarding the rarity of panniculitis in juvenile dermatomyositis and its treatment strategy.